2018
DOI: 10.3727/096504018x15188747585738
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-744 Inhibits Cellular Proliferation and Invasion of Colorectal Cancer by Directly Targeting Oncogene Notch1

Abstract: Accumulated studies have strongly implicated aberrantly expressed microRNAs (miRNAs) in carcinogenesis and cancer progression of various cancers, including colorectal cancer (CRC). Hence, a comprehensive study of miRNAs and their association with CRC may be a promising therapeutic method for patients with this malignancy. MiRNA-744 (miR-744) is abnormally expressed in several types of human cancer. Thus far, little is known about the expression, biological roles and exact mechanisms of miR-744 in CRC. Thus, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…miR-744 expression was downregulated in PTC tissues and cell lines. This observation is consistent with previous findings on the expression profile of miR-744 in colorectal cancer (17), cervical cancer (18) and hepatocellular carcinoma (19); however, miR-744 expression is upregulated in numerous types of human malignancy. For instance, miR-744 is overexpressed in the tissues, cell lines and plasma of pancreatic cancer (26,27).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…miR-744 expression was downregulated in PTC tissues and cell lines. This observation is consistent with previous findings on the expression profile of miR-744 in colorectal cancer (17), cervical cancer (18) and hepatocellular carcinoma (19); however, miR-744 expression is upregulated in numerous types of human malignancy. For instance, miR-744 is overexpressed in the tissues, cell lines and plasma of pancreatic cancer (26,27).…”
Section: Discussionsupporting
confidence: 93%
“…miR-744 is also identified as a tumour suppressor in numerous types of human cancer. For example, miR-744 suppresses cell proliferation and invasion in colorectal cancer (17) and cervical cancer (18). miR-744 upregulation inhibits cell proliferation and promotes cell cycle arrest in hepatocellular carcinoma (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel miR-663 targets are transforming growth factor-β1 [25], proteins PUMA/BBC3 and BTG2 [26], cyclin-dependent kinase inhibitor 2A [27]. The novel miR-744 targets are nuclear factor I X (NFIX) and heterogeneous nuclear ribonucleoprotein C (HNRNPC) [28], oncogene Notch1 [29], matrix metallopeptidase 9 (MMP-9) [30]. As these targets are also related to the cancer development, one cannot be absolutely sure that targeting eEF1A2 is the only mechanism of anti-cancer action of these microRNAs.…”
Section: Regulation Of Eef1a1 and Eef1a2 Mrnamentioning
confidence: 99%
“…[12][13][14] Studies have indicated that miR-744-5p is lowly expressed in multiple cancers, like colorectal cancer, cervical cancer and glioblastoma, and overexpression of miR-744-5p can inhibit cell proliferation, migration, and invasion. [15][16][17] Moreover, miR-744-5p is also down-regulated in EOC cells, its upregulation could induce cell apoptosis. 12 However, the function of miR-744-5p in EOC cell proliferation and metastasis still remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%